2014
DOI: 10.2172/1163269
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Zero Energy Buildings (HZEB) Program - Cross-Sectional Study of Contaminant Levels, Source, Strengths, and Ventilation Rates in Retail Stores

Abstract: This field study measured ventilation rates and indoor air quality parameters in 21 visits to retail stores in California. The data was collected to guide the development of new, science-based commercial building ventilation rate standards that balance the dual objectives of increasing energy efficiency and maintaining acceptable indoor air quality. Data collection occurred between September 2011 and March 2013. Three types of stores participated in this study: grocery stores, furniture/hardware stores, and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…The 3‐year averaged C out was used for calculating C in as described in Equations 1 and 2. For d‐limonene, as data were not available from U.S. EPA, the average outdoor concentrations measured by three studies (Bennett et al., ; Chan et al., ; Siegel et al., ) were used instead.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3‐year averaged C out was used for calculating C in as described in Equations 1 and 2. For d‐limonene, as data were not available from U.S. EPA, the average outdoor concentrations measured by three studies (Bennett et al., ; Chan et al., ; Siegel et al., ) were used instead.…”
Section: Methodsmentioning
confidence: 99%
“…A third way of estimating mean indoor concentrations using maximum-likelihood estimates (MLE) and assuming lognormal distribution also gave similar results. Measurements of VRs were reported in the referenced studies (Bennett et al, 2011;Chan et al, 2014;Persily and Gorfain, 2008;Siegel et al, 2012), with the exception of the California Portable Classroom study (CARB, 2004), where the ventilation rates were not directly measured but calculated from indoor and outdoor CO 2 measurements as per Mendell et al (2013). For the calculation of indoor pollutant concentrations as a function of VRs, measurements of VRs were converted to an air exchange rate, k (1/h), which is the outdoor air supply rate normalized by building volume.…”
Section: Hazard Characterizationmentioning
confidence: 99%
“…Most buildings in the Bennett et al [8] study did not meet California's Title 24 minimum requirements for ventilation on a per area basis. Chan et al (2012Chan et al ( , 2014) conducted a study of retail stores in California, which showed that HCHO concentrations exceeded the OEHHA REL, and that acetaldehyde and acrolein levels exceeded the reference concentration for chronic inhalation exposure (RfC) issued by the U.S. EPA [10] while meeting or exceeding the Title 24 minimum ventilation requirement of 7 L/s person or 1 L/s m 2 . The highest levels of HCHO were measured in apparel stores, and acetaldehyde and acrolein were highest in grocery stores.…”
Section: Introductionmentioning
confidence: 99%
“…More detail descriptions of the stores sampled and data summaries can also be found in Chan et al. ().…”
Section: Introductionmentioning
confidence: 99%
“…Results of measurements of volatile organic compounds (VOCs), ozone, and ventilation rates are described in Chan et al (2014a). More detail descriptions of the stores sampled and data summaries can also be found in Chan et al (2014b).…”
Section: Introductionmentioning
confidence: 99%